Enhancing catalytic activity via metal tuning of zeolitic imidazole frameworks for ring opening polymerization of l-lactide; Applied Catalysis A: General; Vol. 624 - Chaemchuen S. Somboon; Qingping Dai; Wang Jichao; Chenyang Zhu; Klomkliang N. Nikom; Yuan Ye; Chen Cheng; Mirella E. Elkadi; Luo Zhixiong; Verpoort F. V. K. Frensis Valter Kornelius (2021, 2021)
Title screen